Starvation-induced genes of the tomato pathogen Cladosporium fulvum are also induced during growth in planta - Coleman, M.; Henricot, B.; Arnau, J.; Oliver, Richard (1997)
The pathogenicity of fungal pathogens is presumably dependent on genes that are expressed during infection. In order to isolate such genes from the tomato pathogen Cla-dosporium fulvum, and to test the hypothesis that starvation-induced genes are also plant induced, a cDNA library was prepared from mycelia grown in a defined medium and then transferred to a starvation medium. The library was then screened with cDNA probes prepared from starved and replete fungal mycelium. Five unique, differentially expressed cDNAs were isolated from 1,000 clones screened. Northern (RNA) hybridization confirmed that all five were starvation induced. Interestingly, all five were also found to be plant induced. The identity of two of the clones was indicated by partial DNA sequencing as alcohol and aldehyde dehydrogenase. The observed correlation between starvation induction and plant induction is discussed.